2003
DOI: 10.1021/jp0344601
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of CeO2−TiO2 and V2O5/CeO2−TiO2 Catalysts by Raman and XPS Techniques

Abstract: Structural characteristics of ceria−titania and vanadia/ceria−titania mixed oxides have been investigated using X-ray powder diffraction (XRD), Raman spectroscopy (RS), and X-ray photoelectron spectroscopy (XPS) techniques. The (1:1 mole ratio) mixed oxide was obtained by a coprecipitation method, and a nominal 5 wt % V2O5 was deposited over its surface by a wet impregnation technique. Both of the materials were then subjected to thermal treatments from 773 to 1073 K and were characterized by the above-mention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
177
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(190 citation statements)
references
References 57 publications
9
177
1
3
Order By: Relevance
“…[18] This metastable phase could be related to a CeO 2 -TiO 2 mixed oxide with 1:1 atomic ratio, which has been investigated by Reddy et al by various techniques. [19,20] The optical features of cerium makes it a good candidate for colouring applications since the lowest Ce 3+ 4f 1 5d 1 absorption transition takes place in the blue spectral region leading to a yellow-orange body colour. As an example, Ce…”
Section: +mentioning
confidence: 99%
“…[18] This metastable phase could be related to a CeO 2 -TiO 2 mixed oxide with 1:1 atomic ratio, which has been investigated by Reddy et al by various techniques. [19,20] The optical features of cerium makes it a good candidate for colouring applications since the lowest Ce 3+ 4f 1 5d 1 absorption transition takes place in the blue spectral region leading to a yellow-orange body colour. As an example, Ce…”
Section: +mentioning
confidence: 99%
“…The wide application of cerium oxide either as a promoter or as an active catalyst is due to its unique redox and acid-base properties. Labile oxygen vacancies and bulk oxygen species with relatively high mobility are easily formed during the redox shift between Ce 3+ and Ce 4+ under oxidizing and reducing conditions, respectively [15]. Long and Yang studied the performance of cerium oxide catalysts supported on Fe-ZSM-5 [16] and Fe-Ti-PILC [17] for the SCR of NO with NH 3 and concluded that cerium oxide enhanced the oxidation of NO to NO 2 , resulting in an improvement of activity.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the temperature stability and ability of ceria to store and release oxygen, other transition and non transition metal ions (such as Al 3+ , Si 4+ , Ti 4+ and Zr 4+ ) are normally introduced into the ceria cubic structure (Reddy et al, 2003(Reddy et al, , 2005Rynkowski et al, 2000;Masui et al, 2002b). The redox and catalytic properties of CeO 2 are strongly influenced when it is combined with other transition metals.…”
Section: Ceo 2 -Tio 2 Composite As a Catalystmentioning
confidence: 99%
“…A few studies on CeO 2 -TiO 2 composite nanoparticles (Reddy et al, 2003(Reddy et al, , 2005Rynkowski et al, 2000;Masui et al, 2002b) (Rynkowski et al, 2000), and stated the existence of the CeO 2 -TiO 2 composite. Masui et al also synthesized CeO 2 -TiO 2 composite nanoparticles, and reported the deactivation of the thermal and photocatalytic properties of this species by the formation of the CeO 2 -TiO 2 composite (Masui et al, 2002b).…”
Section: Morphology Of Ceo 2 -Tio 2 Compositementioning
confidence: 99%
See 1 more Smart Citation